2016
DOI: 10.1111/ajco.12577
|View full text |Cite
|
Sign up to set email alerts
|

A20 SNP rs77191406 may be related to secondary cancer for rheumatoid arthritis and systemic lupus erythematosus patients

Abstract: These findings suggest that rs77191406 may be a prognostic marker for a high risk for rapid malignancy progression, poor survival and refractory disease and a new molecular marker associated with autoimmune diseases transforming into a secondary cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Interestingly, four of them (rs5029937, rs598493, rs2230926 and rs582757) were also identified in the SS sample, the significance may be the case with rs2230926 TG genotype and rs5029937 GT genotype, which were identified in rare RA cases with poor clinical outcome. More importantly, we also found that rs77191406 was identified in few cases with SLE and RA, and an RA patient who was heterozygous for rs77191406 developed colon cancer 10 years after the RA diagnosis, similarly, one rs77191406 heterozygous SLE patient underwent bladder cancer 5 years after SLE diagnosis . Because, chronic inflammation was a common feature in skin lesion of SS case.…”
Section: Resultssupporting
confidence: 57%
“…Interestingly, four of them (rs5029937, rs598493, rs2230926 and rs582757) were also identified in the SS sample, the significance may be the case with rs2230926 TG genotype and rs5029937 GT genotype, which were identified in rare RA cases with poor clinical outcome. More importantly, we also found that rs77191406 was identified in few cases with SLE and RA, and an RA patient who was heterozygous for rs77191406 developed colon cancer 10 years after the RA diagnosis, similarly, one rs77191406 heterozygous SLE patient underwent bladder cancer 5 years after SLE diagnosis . Because, chronic inflammation was a common feature in skin lesion of SS case.…”
Section: Resultssupporting
confidence: 57%
“…24 Some studies showed that TNFAIP3 could play an important role in immune and inflammatory responses mediated by cytokines. [24][25][26]…”
Section: Tnfaip3 Basic Characteristics Of Tnfaip3mentioning
confidence: 99%
“…Okada et al found that polymorphisms of TNFAIP3 were common to both rheumatoid arthritis and Hodgkin’s lymphoma [104]. In the only study examining TNFAIP3 in SLE, Zhu and Zhou [105] reported that two of 37 patients with SLE were heterozygous for an A20 gene polymorphism ( rs77191406 ); one developed bladder cancer with liver metastases while the other had severe SLE, including central nervous system and renal involvement. Hence, rs77191406 may be an important prognostic marker for malignancy risk and SLE severity.…”
Section: Factors Potentially Mediating Riskmentioning
confidence: 99%